If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 13 = 5x + -6 Reorder the terms: 13 + 8x = 5x + -6 Reorder the terms: 13 + 8x = -6 + 5x Solving 13 + 8x = -6 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 13 + 8x + -5x = -6 + 5x + -5x Combine like terms: 8x + -5x = 3x 13 + 3x = -6 + 5x + -5x Combine like terms: 5x + -5x = 0 13 + 3x = -6 + 0 13 + 3x = -6 Add '-13' to each side of the equation. 13 + -13 + 3x = -6 + -13 Combine like terms: 13 + -13 = 0 0 + 3x = -6 + -13 3x = -6 + -13 Combine like terms: -6 + -13 = -19 3x = -19 Divide each side by '3'. x = -6.333333333 Simplifying x = -6.333333333
| -3(4a-8)=-36 | | 9x-5=4(x-5) | | y=-5x^2+3x-4 | | 8(7)-96= | | 1z+3=29-2z | | 2t-2=3t+6 | | 2t-2=3t+2 | | -3a(-10)=16 | | (x)(2x-3)=27 | | T-1/4=11/4 | | 2x+-6=8 | | h(t)=-16t^2+79t+5 | | y=(2x-1)(3x+2) | | 4t=16.11-0.0062y | | -x(7)=-40 | | y=(2x-1)(3x-1) | | 4-√-12/4 | | t=16.11-0.0062 | | -7t^2+7t+8t^3-t^3+15t^2-4t= | | 5+8(X-2)=11-7(X-8) | | x(x-6)-x^2-5x-7=0 | | p(x)=(500-x)/20 | | X/100=27/64 | | x(x-6)=x^2+5x+7 | | -4(x-9)=-9x+6 | | -7(t-8)-(t+3)=10 | | X+6y+4z=-13 | | (4x+2)(2x+1)=0 | | x=5000/40/x-10/x | | 4x-9=-18 | | .15x=3800 | | -3x-Y-z=-6 |